Tyrosine Kinase Inhibitors Available for Chronic Myeloid Leukemia: Efficacy and Safety - García-Gutiérrez, Valentín; Hernández-Boluda, Juan Carlos (Frontiers in Oncology, 2019)
Chronic myeloid leukemia (CML) is currently a disease in which patients can enjoy a near normal life-expectancy. However, since the majority of patients will need to remain on treatment indefinitely, physicians in care of CML patients need be familiar with the indications and toxicities of all approved tyrosine kinase inhibitors (TKI). In clinical practice, there are five TKI (imatinib, nilotinib, dasatinib, bosutinib, and ponatinib) that are available in different scenarios and have distinct safety profiles. Decisions regarding first line treatment must be based on CML risk, comorbidities, and patients expectations. Despite the excellent outcome, half of the patients will eventually fail (due to intolerance or resistance) to first line treatment, with many of them requiring a third or even further lines of therapy. When selecting for such patients, it is essential to distinguish between failure and intolerance to previous TKIs. In the present review, we will address all these issues from a practical point of view